(untitled) (Ágora UNLaR, 2019)
Como surge de su título, el objetivo de mi presentación es aportar a la caracterización de la narrativa femenina estadounidense del nuevo milenio. Debo aclarar que este estudio forma parte de uno más amplio que aspira a caracterizar el “estilo de cultura” del nuevo milenio. Concentré este estudio en las novelas escritas por mujeres en el Siglo XXI que ganaron el Pulitzer Prize. Trabajé en base a la hipótesis de que la ficción femenina del Siglo XXI se aleja de los homenajes intertextuales paródicos posmodernos -que requerían un lector iniciado en la historia literaria y se acerca más bien a las estrategias narrativas del objetivismo modernista o bien de la novela del Siglo XIX, novela de intrigas, con tramas detectivescas en muchos casos, bildungsromans que en el Siglo XXI incorporan, naturalmente, las nuevas tecnologías. AMERICAN FEMININE NARRRATIVE OF THE NEW MILLENNIUM Abstract As expresseod in the title, the aim of my presentation is to contribute to characterize the American feminine narrrative of the new millennium, this study being a contribution to a broader one aspirng to characterize the “style of culture” of the new millennium. To this end, I concentrated my analysis on the novels written by women in the XXIst Century that won the Pulitzer Prize. I worked on the hypothesis that XXIst Century feminine fiction departs from the postmodern intertextual parodic homages -which demanded the presence of a competent reader with a sound knowledge of literary history-and is more akin to the narrative strategies of modern objectivism or those of the XIXth Century novel, a novel of intrigues, with detective plots on many occasions, bildungsromans that in the XXIst Century incorporate the new technologies. Key words: american feminine fiction; new millennium; narrative strategies